2015
DOI: 10.1080/09540121.2015.1032207
|View full text |Cite
|
Sign up to set email alerts
|

State-level spending on health care and social services for people living with HIV/AIDS in the USA: a systematic review

Abstract: Every year for the past decade, approximately 50,000 people have been diagnosed with HIV or AIDS in the USA, and the incidence of HIV/AIDS varies considerably from state to state. Studies have shown that health care services, most notably treatment with combination antiretroviral therapy, can help people living with HIV/AIDS (PLWHA) live healthier, longer lives, and prevent the spread of HIV from person to person. In addition, social services, such as housing support and provision of meals, have also shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Studies have also demonstrated that increased spending on healthcare services, such as testing, antiretroviral treatment, and primary patient care also leads to reductions in HIV/AIDS diagnoses and mortality [ 9 ]. Yet less is known about the association between spending on nonmedical services, such as public health and social services, and HIV/AIDS diagnoses and AIDS deaths, or about how variation in social service and public health spending may explain state-level variation in these HIV/AIDS outcomes across the United States [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated that increased spending on healthcare services, such as testing, antiretroviral treatment, and primary patient care also leads to reductions in HIV/AIDS diagnoses and mortality [ 9 ]. Yet less is known about the association between spending on nonmedical services, such as public health and social services, and HIV/AIDS diagnoses and AIDS deaths, or about how variation in social service and public health spending may explain state-level variation in these HIV/AIDS outcomes across the United States [ 10 ].…”
Section: Introductionmentioning
confidence: 99%